(untitled) (Construction Economics and Building, 2019)
A comprehensive review of megaproject performance propositioned the issues leading to project failure as behavioral. Project failure linked cost overruns and schedule delays to acts of delusion and deception, citing the ability to learn lessons, and the misalignment of incentives as influencing factors. A mixed-methods study was designed to gain insight into the decision-making behaviors of undergraduate civil engineers, and the role that education could play in enhancing decision-making. A co-curricular intervention led to qualitative exploration of decision-making in civil engineering undergraduates. Motivation featured heavily, particularly a conflict between interest and enjoyment, and the reward structures of traditional education and industry. Results led to a quantitative measure of intrinsic motivation and critical thinking ability. Findings from the educational environment have implications for industry and led to recommendations regarding the importance of autonomy and relatedness, to a megaproject environment.